2016
DOI: 10.1186/s12939-016-0316-x
|View full text |Cite
|
Sign up to set email alerts
|

Narrative review of women’s health in Iran: challenges and successes

Abstract: BackgroundIn each society, the health of women in different periods may be endangered by an unequal distribution of resources, facilities, and gender prejudices. The present study evaluated the time trend of Iranian women’s health between 1990 and 2013.MethodsThis narrative review includes an integration and descriptive summary of the existing evidence on trends and criteria of different aspects of women’s health from social determinant point of view. The evidence was drawn from peer-reviewed, cross-national o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 29 publications
0
28
1
Order By: Relevance
“…Also, the number of health facilities is not enough in remote rural areas of this province. Furthermore, more than 50% of maternal mortalities in deprived provinces are reported to be preventable …”
Section: Women's Health and The Right To Health In Iranmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, the number of health facilities is not enough in remote rural areas of this province. Furthermore, more than 50% of maternal mortalities in deprived provinces are reported to be preventable …”
Section: Women's Health and The Right To Health In Iranmentioning
confidence: 99%
“…Limited access to reproductive health information and contraceptives can result in unwanted pregnancies, sexually transmitted diseases, HIV infection, and pregnancy‐related illnesses and death. Studies showed that the prevalence of HIV/AIDS among Iranian women has increased by 550% from 2007 to 2015 . Most of these women are infected via having sex with their partners .…”
Section: Women's Health and The Right To Health In Iranmentioning
confidence: 99%
See 2 more Smart Citations
“…A symbol of such collaboration between the community and first level health system can be seen in epidemics and delivering healthcare. Another sign of this collaboration is the large number of female health volunteers, who are working with Behvarzes to promote community health (5). It is obvious that companionship of other sectors' developmental programs has resulted in an overall socioeconomic development of the rural population and has made the improvement of health indicators sustainable.…”
mentioning
confidence: 99%